Changes of phenolic content in rapeseed during preliminary drying (Journal of Oilseed Brassica, 2026)
Drying of rapeseed represents one of the most important elements in the complexity of actions defined as the “post-cropping” process. This work investigates how drying of the rapeseed at low and high temperature influences the bioactive compounds (phenolic acids). Samples of rapeseed (Kronos and Lisek variety) were dried at 60, 80, 100, and 120C and low temperature (layer 2 and 12). In methanolic extracts total phenolic content was determined using Folin-Ciocalteu reagent and composition of free phenolic acids was determined by HPLC. Obtained results showed that the most unfavourable influence on the native hydrophilic antioxidant content was observed after drying at 60 and 80oC. Seed dried at these temperatures are characterized by highest decrease of total phenolic compounds and free phenolic acid content. Probably it is caused by the activity of enzymes (phenoloxidaze) that display optimal functional activity at this temperature